Metaphorical reasoning with an economical set of mappings - Wallington, A. M.; Barnden, J. A.; Glasbey, S. R.; Lee, M. G. (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
This paper discusses the nature of the metaphorical transfer from the source domain to the target domain. More specifically, it explores the question as to how the mapping links between features of the source and the target are created. It is argued that, for many metaphors, it is incorrect to assume that all the elements of the source domain map to elements of the target domain, and that a much more economical set of mappings should be used instead.